Differential expression of the Bcl-2 and Bax isoforms in CD19 positive B-lymphocytes isolated from patients diagnosed with chronic lymphocytic leukaemia - Ghassemifar, Reza; Forster, L.; Finlayson, J.; Calogero, T.; Augustson, B.; Joske, D.; Cull, G. (2012)
Aim: To examine the relative gene expression levels of the anti-apoptotic Bcl-2a and ß isoforms and the pro-apoptotic Baxa and ß isoforms in patients with chronic lymphocytic leukaemia (CLL) and healthy controls (HC). Methods: Peripheral blood was obtained from 36 patients diagnosed with CLL and 10 HC. CD19+ B-lymphocytes were isolated using an antibody coupled magnetic bead isolation system; from these cells the total RNA was isolated and purified. The relative levels of gene expression were examined by quantitative real-time polymerase chain reaction (qReTi-PCR) using primers specific for each isoform. Results: Bcl-2a and Baxa are expressed at higher levels than their ß-isoforms in CLL and HC. Bcl-2a, Bcl-2ß and Baxb expression is increased in CLL while Bax-a is expressed at similar levels to HC. The Bcl-2a/Bcl-2ß ratio is similar in CLL and HC. The Bcl-2a/Baxa ratio is increased in CLL when compared with HC. Conclusion: Bcl-2a and Baxa appear to be the dominant antiand pro-apoptotic isoforms in CLL. The Bcl-2a/Baxa ratio is increased in CLLwhile the Bcl-2a/Bcl-2ß ratio is similar to HC.